Kajian Time Series TB.Paru BTA(+) di Bandar Lampung Tahun 2021-2030 - Helmy, Helina; Usmann, Sarip; Sujito, Enro (Universitas Malahayati Bandar Lampung, 2025)
Background: Aerosols are solid or liquid suspensions that float in the atmosphere. Aerosol size is 0.001-100 µm. Aerosols <2.5 µm are fine particles, while >2.5 µm are coarse particles. The disease spreads through the air. Tuberculosis is still a major global health problem because it causes deaths from infectious diseases with a low ability to anticipate the incidence of BTA (+) Pulmonary TB in the city of Puskesmas working area in Bandar Lampung.Objective: To know the trend of BTA positive pulmonary TB disease in 2015-2021 based on time. Furthermore, it is predicted in 2021 until 2030. The type of research is descriptive study research using time series analysis. The population and sample in this study were all BTA (+) pulmonary TB case data.Methods: Time series analysis design based on time-based observation. Type of quantitative descriptive research. The subjects in this study were cases of patients with BTA positive pulmonary TB sourced from the Health Office in Bandar Lampung in 2019-2022. The data was analyzed using Brown's double exponential smoothing forecasting method. R squat can be categorized as strong (>0.75), moderate (<0.5) and weak (<0.25). This means that the more R squat approaches the number one, the better the memorization.Results: The results of this study indicate that the trend of BTA (+) Pulmonary TB cases is predicted to continue to increase.Conclusion: Time model with Brown's double exponential smoothing method. Able to forecast Pulmonary TB BTA (+) in 2015-2020, using the equation, the results of forecasting the number of Pulmonary TB cases in 2021-2030 with Brown's double exponential smoothing method obtained experience a linear trend. Keywords: Time Seriess, TB.Paru BTA(+), Tren kasus